Information Search Patterns in Complex Tasks - Vakkari, Pertti (Journal of Information and Knowledge, 2023)
This paper seeks to analyze information search process in complex tasks1. Complex tasks are larger tasks, which lead people to engage in search tasks for finding information to advance those tasks. Search process consists of activities from query formulation to working with sources selected for task outcome. This paper approaches task performance from the cognitive point of view conceptualizing it as changes in knowledge structures. These structures consist of concepts and their relations representing some phenomenon. Changes in knowledge structures are associated to query formulation and search tactics, selecting contributing sources and working with sources for creating task outcome. As a result, hypotheses concerning associations between changes in knowledge structures and search behaviors are suggested. The paper also presents some ideas for success indicators at various stages of search processes.